(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
Practical work is an indispensable part of science, technology, engineering, and mathematics education. The transition to remote online teaching during COVID-19 deemed it necessary for practical work to be undertaken virtually and teachers had to use new strategies to engage learners in practical work. In South African schools, many teachers and learners cope with poorly resourced laboratories. The argument advanced in this paper is that virtual platforms can resolve the lack of physical resources and provide equitable learning opportunities for learners, provided teachers and learners are trained to use technology. This research answered the following question: What are STEM hons students’ experiences using technology during online practical work during COVID-19 conditions? The location of the study was Richwood Teacher Training Institution in, South Africa. Thirty-six STEM Hons students were the participants of the study. Data was collected via reflective journals and semi-structured interviews. The findings suggest that conducting practicals via virtual laboratories, simulations, and field trips helps obviate the lack of resources and provides epistemic access to learners to quality learning materials and activities. Virtual practicals allowed female learners to experience all process skills, prevented the epistemic exclusion of female learners and addressed issues of social justice. Hands-on practical work can be conducted virtually, and learners can experience a variety of process skills. The novel findings of this study illustrate how to enact STEM teaching in developing countries, address issues of equity and leverage technology to enhance practice in STEM subjects post-COVID.